A Commentary on the Council of Europe Convention on Action against Trafficking in Human Beings (2020)
This comprehensive Commentary provides the first fully up-to-date analysis and interpretation of the Council of Europe Convention on Action against Trafficking in Human Beings. It offers a concise yet thorough article-by-article guide to the Convention's anti-trafficking standards and corresponding human rights obligations. This Commentary includes an analysis of each article's drafting history, alongside a contextualisation of its provisions with other anti-trafficking standards and a discussion of the core issues of interpretation.